ETIKA POLITIK ARISTOTELES DAN RELEVANSINYA BAGI KEMAJEMUKAN RELIGIUS DI INDONESIA - Anto, Puji (Living Islam: Journal of Islamic Discourses, 2022)
Aristotle's political philosophy is very important and relevant to discuss today, because it was the foundation of modern political theory. Aristotle provided the concept of the state with the best possibilities in reality, not on the basis of an abstract ideal order. From his studies Aristotle concluded that the most practicable state system is a constitutional government with the active participation of its citizens, or what he termed "Polity". A form of government which is a combination of constitutional democracy with certain aristocracy. The concept of constitutional democratic governance of Aristotelian ideas is currently widely used in the practice of state administration in the world, with a variety of variations and modifications. In his epistemology, Aristotle also classifies politics as a practical science, therefore politics requires the good and honest will of the politicians, more than merely perfect reason and knowledge. Filsafat politik Aristoteles sangat penting dan relevan untuk dibahas saat ini, karena merupakan landasan teori politik modern. Aristoteles memberikan konsep negara dengan kemungkinan terbaik dalam kenyataan, bukan berdasarkan tatanan ideal yang abstrak. Dari kajiannya Aristoteles menyimpulkan bahwa sistem negara yang paling praktis adalah pemerintahan konstitusional dengan partisipasi aktif warganya, atau yang disebutnya “Polity”. Suatu bentuk pemerintahan yang merupakan perpaduan antara demokrasi konstitusional dengan aristokrasi tertentu. Konsep pemerintahan demokrasi konstitusional gagasan Aristoteles saat ini banyak digunakan dalam praktik ketatanegaraan di dunia, dengan berbagai variasi dan modifikasi. Dalam epistemologinya, Aristoteles juga mengklasifikasikan politik sebagai ilmu praktis, oleh karena itu politik membutuhkan kehendak baik dan jujur para politisi, lebih dari sekedar akal dan pengetahuan yang sempurna.Kata Kunci: Pemikiran Politik, konsep Etika, Aritoteles.